The TLR2 Binding Neisserial Porin PorB Enhances Antigen Presenting Cell Trafficking and Cross-presentation - Michael L. Reiser (Nature Portfolio, 2017)
Abstract TOLL-like receptor (TLR) ligands activate both innate and adaptive immune cells, while modulating the cellular immune response. The outer membrane protein (OMP) from Neisseria meninigitidis, PorB, is a naturally occurring TLR2 ligand and functions as an adjuvant. Here, we demonstrate that PorB increases the level of OVA in the endo-/lysosomal cellular compartment of BMDCs, increases antigen presenting cell (APC) trafficking to draining lymph nodes, and enhances antigen cross-presentation. PorB is capable of mounting an antigen specific T cell response by efficiently stimulating antigen cross-presentation in vivo and in vitro assessed by BMDC OT-I cocultivation assays. The enhanced antigen cross-presentation and the increased APC recruitment to secondary lymphoid tissues expand the scope of known adjuvant effects of PorB on the immune system. Our findings lead to a better understanding of how TLR-ligand based adjuvants can alter and modulate immune responses.